Do Elevated Serum C-Reactive-Protein Levels Excuse Delayed Surgery for Femoral Neck Fractures? - Roberta Laggner; Benan Taner; Jennifer Straub; Thomas Manfred Tiefenböck; Harlad Binder; Thomas Sator; Stefan Hajdu; Reinhard Windhager; Christoph Böhler (MDPI AG, 2023)
In elderly patients with femoral neck fractures, preoperative serum C-reactive protein (CRP) values might be elevated due to active infections. Although there are limited data on CRP as a predictor of periprosthetic joint infection (PJI), out of concern, this could lead to delayed surgery. Therefore, we aim to investigate whether elevated serum-CRP levels justify delayed surgery for femoral neck fractures. A retrospective analysis was performed of the records of patients undergoing arthroplasty who were found to have an elevated CRP level of 5 mg/dL or more between January 2011 to December 2020. The patients were stratified to three groups, according to initial serum CRP levels at a cut off of 5 mg/dL and the time between admission and surgery (<48 vs. ≥48 h after admission). This study revealed that the patients with elevated serum CRP levels and delayed surgery showed a worse survival rate and significantly more postoperative complications than the patients on whom surgery was performed immediately. There were no significant differences in terms of PJI and prolonged wound healing in the inter-group comparison. Therefore, delays to surgery on the basis of elevated CRP values offer no benefits to patients with femoral neck fractures.